Iconic gesture in normal language and word searching conditions: A case of conduction aphasia. (October 2013) - Pritchard, Madeleine; Cocks, Naomi; Dipper, Lucy
Abstract: Although there is a substantive body of research about the language used by individuals with aphasia, relatively little is known about their spontaneous iconic gesture. A single case study of LT, an individual with conduction aphasia indicated qualitative differences between the spontaneous iconic gestures produced alongside fluent speech and in tip of the tongue states. The current study examined the iconic gestures produced by another individual with conduction aphasia, WT, and a group of 11 control participants. Comparisons were made between iconic gestures produced alongside normal language and those produced alongside word-searching behaviour. Participants recounted the Tweety and Sylvester cartoon Canary Row . All gesture produced was analysed qualitatively and quantitatively. WT produced more iconic gestures than controls accompanying word searching behaviour, whereas he produced a similar frequency of iconic gestures to control participants alongside normal language. The iconic gestures produced in the two language contexts also differed qualitatively. Frequency of iconic gesture production was not affected by limb apraxia. This study suggests that there are differences between iconic gestures that are produced alongside normal language and those produced alongside word-searching behaviour. Theoretical and clinical implications of these findings are discussed.